PENGARUH CORE TAX ADMINISTRATION SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Silmi Silmi; Rahmat Kurniawan; Nadya Putri Nasha; Luthfan Fadila Yunda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Digital transformation in tax administration systems has become an important strategy for improving tax efficiency and compliance. This study aims to analyze the effect of Core Tax Administration System (CTAS) implementation on individual taxpayer compliance in Indonesia. The study employed a quantitative survey approach using questionnaires distributed to 128 respondents. Instrument validity and reliability were assessed using Pearson correlation and Cronbach’s Alpha, while simple regression analysis was used to test the relationship between the variables. The results show that all CTAS and taxpayer-compliance items have significant correlations with their respective total scores (r 0.173; p 0.01), with Cronbach’s Alpha values of 0.649 and 0.664, indicating adequate instrument reliability. Regression analysis shows that CTAS implementation has a positive and significant effect on taxpayer compliance (R² = 0.224; F = 36.314; p 0.001), while the model satisfies normality and homoscedasticity assumptions and shows no autocorrelation (Durbin-Watson = 1.989). These findings indicate that digital tax administration systems such as CTAS can significantly improve taxpayer compliance, although other factors also contribute.Keywords: CoreTax, Individual Taxpayers, Tax Compliance, Tax Digitalization, Tax Administration System